The clinical impact of multiple prevention strategies for respiratory syncytial virus infections in infants and high-risk toddlers in the United States. Issue 42 (6th October 2022) - Ektare, Varun; Lang, John; Choi, Yoonyoung; Finelli, Lyn
Highlights: Respiratory syncytial virus (RSV) remains a leading cause of medically-attended (MA) lower respiratory tract infection (LRTI) and non-LRTI episodes in the US in infants and children. The vast majority (>80 %) of medically-attended RSV LRTIs and non-LRTIs occur among healthy full-term infants. The long-acting mAb intervention is the most effective at reducing the number of MA-RSV episodes, especially in older infants (≥6 months old). Our model is unique in simultaneously accounting for gestational age at birth, birth month, and RSV seasonality. Abstract: Background: Respiratory syncytial virus (RSV) remains a leading cause of medically-attended acute respiratory infection in infants and children. With multiple preventative interventions under development, accurate estimates of health care resource utilization are essential for policy decision making. Methods: We developed a literature-based decision-tree model that estimated annual medically-attended RSV (MA-RSV) lower respiratory tract infection (LRTI) and non-LRTI episodes in the US for all infants and for high-risk toddlers. The model accounted for the gestational age and birth-month of infants, and the seasonal variation in RSV incidence. The impact of no prophylaxis, palivizumab, maternal vaccine, and long-acting monoclonal antibody (mAb) interventions was estimated. Results: We estimated 1.23 million (range: 0.96 million–1.40 million) annual MA-RSV LRTI/non-LRTI episodes comprised of 1.19 million (range: 0.93 million–1.36 million) emergency department (ED) and outpatient visits, and 39, 040 (range: 32, 726–45, 851) hospitalizations. Outpatient and ED visits were comprised of 586, 034 (range: 430, 595–718, 868) LRTIs and 608, 733 (range: 495, 705–644, 658) non-LRTIs. The long-acting mAb intervention resulted in the greatest number of averted outpatient and ED episodes (310, 997 [53%] LRTIs; 284, 305 [47%] non-LRTIs) and hospitalizations (21, 845 [56%]). Full-term infants constitute the highest proportion of episodes across all interventions. Conclusions: MA-RSV disease is substantial in infants and high-risk toddlers. Long-acting mAbs are most effective at reducing the number of MA-RSV LRTI/non-LRTI episodes, and the only intervention that prevents disease in older infants (≥6 months old).